In vivo astrocytic Ca2+ signaling in health and brain disorders. (September 2013) - Ding, Shinghua
Astrocytes are the predominant glial cell type in the CNS. Although astrocytes are electrically nonexcitable, their excitability is manifested by their Ca 2+ signaling, which serves as a mediator of neuron–glia bidirectional interactions via tripartite synapses. Studies from in vivo two-photon imaging indicate that in healthy animals, the properties of spontaneous astrocytic Ca 2+ signaling are affected by animal species, age, wakefulness and the location of astrocytes in the brain. Intercellular Ca 2+ waves in astrocytes can be evoked by a variety of stimulations. In animal models of some brain disorders, astrocytes can exhibit enhanced Ca 2+ excitability featured as regenerative intercellular Ca 2+ waves. This review first briefly summarizes the astrocytic Ca 2+ signaling pathway and the procedure of in vivo two-photon Ca 2+ imaging of astrocytes. It subsequently summarizes in vivo astrocytic Ca 2+ signaling in health and brain disorders from experimental studies of animal models, and discusses the possible mechanisms and therapeutic implications underlying the enhanced Ca 2+ excitability in astrocytes in brain disorders. Finally, this review summarizes molecular genetic approaches used to selectively manipulate astrocyte function in vivo and their applications to study the role of astrocytes in synaptic plasticity and brain disorders.